Noachic traditions in the Book of Parables: Two parallels from the Dead Sea Scrolls - Feldman, Ariel (Journal for the study of the pseudepigrapha, 2021)
This note draws attention to two passages from the so-called Noachic interpolations in the Book of Parables where Noah traditions embedded in Qumran scrolls may provide helpful parallels. First, it suggests that the dating of the vision in 1 En. 60:1 is illuminated by a comparison to the Flood chronology in 4Q252. Second, it points out a similar use of Isa 24:18–20 in 1 En. 65:1–5, 9 and 4Q370. In both instances, the suggested parallels highlight the Parables’ use of the Flood as a prototype of an eschatological judgment.